2004
DOI: 10.1002/bjs.4641
|View full text |Cite
|
Sign up to set email alerts
|

Damage control in the abdomen and beyond

Abstract: Damage control surgery, sometimes known as 'damage limitation surgery' or 'abbreviated laparotomy', is best defined as creating a stable anatomical environment to prevent the patient from progressing to an unsalvageable metabolic state. Patients are more likely to die from metabolic failure than from failure to complete organ repairs. It is with this awareness that damage control surgery is performed, enabling the patient to maintain a sustainable physiological envelope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 57 publications
0
40
0
8
Order By: Relevance
“…Stent-grafts may also be used to treat traumatic dissections in the remaining part of the aorta. (17)(18)(19) Standards urgical practice teaches that the best operation for ap atient is one, definitive procedure. Damage control surgical principles teach the exact opposite, namely that the patient with major exsanguinating injuries is morel ikely to die of metabolic failuret han from failuret od efinitive repair.D CS is the principle of surgically maintaining the oxygen transport in the injured patient who is deteriorating and will not tolerate longlasting, definitive surgery.…”
Section: Splenic Injuriesmentioning
confidence: 99%
“…Stent-grafts may also be used to treat traumatic dissections in the remaining part of the aorta. (17)(18)(19) Standards urgical practice teaches that the best operation for ap atient is one, definitive procedure. Damage control surgical principles teach the exact opposite, namely that the patient with major exsanguinating injuries is morel ikely to die of metabolic failuret han from failuret od efinitive repair.D CS is the principle of surgically maintaining the oxygen transport in the injured patient who is deteriorating and will not tolerate longlasting, definitive surgery.…”
Section: Splenic Injuriesmentioning
confidence: 99%
“…Um conceito importante que precisa ser incorporado é a abordagem cirúrgica com "controle de danos" (Damage control) ou laparotomia abreviada. Trata-se da manutenção de um ambiente anatômico estável para impedir a progressão das alterações fisiológicas para um estado metabólico irreversível, uma vez que os pacientes morrem mais freqüentemente de déficits funcionais (hipotermia, acidose metabólica intratável e estado de incoagulabilidade sanguínea) do que do reparo anatômico completo dos órgãos 30 . A opção por esta abordagem cirúrgica deve ser tomada tão logo se constate os déficits metabólicos do paciente e faça os controles dos sangramentos e das contaminações intestinais mais grosseiras.…”
Section: 2-tratamento Cirúrgicounclassified
“…É feita a compressão da cavidade peritoneal, com os órgãos mantidos na sua posição anatômica utilizando-se compressas cirúrgicas (packing abdominal) e, é realizada a síntese temporária da parede abdominal. O paciente é internado em ambiente de terapia intensiva para controle dos déficits fisiológicos e, em 24 a 48 horas, após o controle da temperatura corpórea, da coagulação sangüínea e da acidose metabólica, será levado novamente ao centro cirúrgico para a correção anatômica definitiva das lesões 30 . Outra abordagem cirúrgica que pode ser utilizada em situações especiais são as relaparotomias programadas (second look), principalmente, no caso de dúvidas sobre a viabilidade de alças intestinais, anastomoses com risco de deiscência, necrosectomias e infecções peritoneais graves 30 .…”
Section: 2-tratamento Cirúrgicounclassified
“…[4,5] Trauma-associated coagulopathy was originally thought to be primarily due to hypothermia, acidosis and consumption/dilution of clotting factors. [6] Current studies have revealed that neurohormonal activation, systemic inflammation and widespread endothelial damage may similarly have an important influential role, and the etiology of traumarelated coagulopathy is multifactorial. [7,8] Much mystery still surrounds changes in coagulation taking place in the period after injury.…”
Section: Introductionmentioning
confidence: 99%